USM RECEIVES OFFICIAL VISIT FROM AUSTRALIAN HIGH COMMISSIONER - MPRC, Pusat Media & Perhubungan Awam (2017)
USM, PENANG, 20 February 2017 Universiti Sains Malaysia (USM) Deputy ViceChancellor (Research and Innovation) Professor Dato' Dr. Muhamad Jantan recently hosted a roundtable discussion meeting between USM and delegates from the Australian High Commission at the Chancellory Conference Room, Chancellory Building, USM.